(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
With the increasing effect of globalization andtechnology, organizations have started to use information systems in variousfunctions and departments in the last decades. Human resources management isone of the departments that mostly use management information systems. HRinformation systems support activities such as identifying potential employees,maintaining complete records on existing employees and creating programs todevelop employees talents and skills. HR systems help senior management toidentify the manpower requirements in order to meet the organization’s longterm business plans and strategic goals. Middle management uses human resourcessystems to monitor and analyze the recruitment, allocation and compensation ofemployees. Operational management uses HR systems to track the recruitment andplacement of the employees. HRIS can also support various HR practices such asworkforce planning, staffing, compensation programs, salary forecasts, paybudgets and labour/employee relations. The results of the research givevaluable insights about the success and effectiveness of HRIS in organizations.Also the results of the study are discussed in the context of the theoreticaland empirical background of MIS and HRIS.